Abundance estimates and trends for Antarctic minke whales (Balaenoptera bonaerensis) in Antarctic Areas IV and V for the period 1989/90–2004/05 - Hakamada, Takashi; Matsuoka, Koji; Nishiwaki, Shigetoshi; Kitakado, Toshihide (J. Cetacean Res. Manage., 2023)
The Japanese Whale Research Programme under Special Permit in the Antarctic (JARPA) conducted sighting surveys during the 1989/90 to 2004/05 austral summer seasons (mainly in January and February), alternating between IWC management Areas IV (70°E–130°E) and V (130°E–170°W), both south of 60°S each (split-)year. These data are analysed to obtain abundance estimates for Antarctic minke whales (Balaenoptera bonaerensis) in these Areas. The estimates are calculated by standard line transect analysis methods using the program DISTANCE under the assumption that g(0) = 1. Annual rates of increase in abundance are estimated using log-linear models. The analyses take several recommendations from the 2006 JARPA Review Meeting into consideration. Those addressed here aim to: (a) improve the point estimates of abundance and their precision; and (b) evaluate (through sensitivity tests) the effect of different factors associated with the JARPA survey on the estimates of abundance and trend. GLM models are used to adjust for different strata being surveyed at different times of year over the duration of JARPA, with model selection being based on AICc . Abundance estimates for Area IV range from 16,562 (CV = 0.542) in 1997/98 to 44,945 (CV = 0.338) in 1999/00, while those for Area V range from 74,144 (CV = 0.329) in 2004/05 to 151,828 (CV = 0.322) in 2002/03. Estimates of the annual rates of increase in abundance are 1.8% with a 95% CI of [–2.5%, 6.0%] for Area IV and 1.9% with a 95% CI of [–3.0%, 6.9%] for Area V. Estimates of these trends are robust to the effects of changes in survey timing, the shapes of the shoulders of detection functions, portions of survey tracklines following the ice edge, parts of the Areas in which no survey took place and poor coverage within some strata. Adjustments to allow for the g(0) being less than 1 are made by the application of a regression model, developed from the results of the Okamura-Kitakado (OK) method estimate of minke whale abundance from the IDCR-SOWER surveys, which provides estimates of g(0) from the statistics of the minke whale school size distribution in a stratum. With this adjustment, abundance estimates increase by an average of 32,333 (106%) for Area IV and 89,245 (86%) for Area V, while the estimates of annual rates of increase and their 95% CIs change slightly to 2.6% [–1.5%,6.9%] for Area IV and 1.6% [–3.4%,6.7%] for Area V.